Nikos Papastergiadis: The Cultures Of The South As Cosmos - Papastergiadis, Nikos (The Nordic Journal of Aesthetics, 2017)
As the Global South is increasingly interpenetrated by neo-liberal and authoritarian regimes the idea of the South as a site of emancipatory resistance and exotic cultural difference has ended. This article offers an alternative route into the cultures of the South. It focuses on the shifting forms of the South in contemporary visual art and outlines the possibilities of non-coercive forms of cultural exchange and the cartographies of a cosmopolitanism from below. This perspective on the South is most evident in the stories of embodied solidarity that stand in contrast to top down visions of socio-economic development and cultural homogenization.